ARRANGEMENT OF NATIONAL SONGS FOR ELEMENTARY SCHOOL STUDENTS' DRUMBAND MUSICAL PERFORMANCES - Arizal Dwi Kurniawan; Destrinelli; Muhammad Sofwan (RADJA PUBLIKA, 2025)
The purpose of this study was to produce an arrangement by describing the development of the product, knowing the level of validity, the level of practicality, and presenting national songs for elementary school students' drumband music games. The development research used a 4D (four-D) model, the test subjects in this study were students who were members of a drumband group totaling 19 students. The results of the study are firstly the process of developing national songs for drumband music games through four stages: define, design, development, and disseminate. The development product was made into a prototype of musical notation scores using the Sibelius Ultimate application. The level of validity of the learning product is as follows, the feasibility of the material aspect with an average of 5 is included in the very valid category, the learning aspect with an average of 4.6 is included in the very valid category. While the level of practicality is as follows, the results of teacher responses with an average of 4.7 are included in the very practical category. Drumband music games with national songs are very important to develop because of their uniqueness, meaningfulness, and usefulness for students' development needs.